FOMSUMERISM : MENGEMBANGKAN PERILAKU CONFORMITY CONSUMPTION DENGAN MEMANFAATKAN FEAR OF MISSING OUT KONSUMEN - Widyasari, Suzy; Soliha, Euis; Santoso, Ignatius Hari (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2021)
This research is purposed to analyze the effect of FoMO to the conformity consumption behavior. Total samples used in this research is 150 respondents which comprised of 47 respondents with 5-7 times accessing social media and the rest of it more than 8 times accessing social media in a day. Using the convinience and purposive sampling technique, researcher gained 100%% response rate. All data are examined by multiple regression and provide significant effect of anxiety of isolation as the predictor of conformity consumption behavior.